ID: 62. Issue 1 (November 2015) - Bae, Heekyong; Valencia, Julio C.; Hodge, Deborah L.; Sanford, Michael E.; Hanson, Charlotte A.; Back, Tim; Karwan, Megan; Feng, Dechun; Gao, Bin; Park, Ogyi; Tsuneyama, Koichi; Leung, Patrick S.; et al.
<x xml:space="preserve">Abstract</x> Primary biliary cirrhosis (PBC, now called autoimmune cholangitis) is an autoimmune liver disease and occurs primarily in women (<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7nzr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />></alternatives>90%), eventually leads to liver failure. IFN-gamma is elevated in patients with PBC, but the functional role of IFN-gamma on PBC is not known. Here, we characterized the distinctive pathological phenotype of PBC in a mouse model of chronic IFN-gamma expression generated by deletion of the IFN-gamma 3′ UTR AU-rich element (ARE-Del). Consistent with clinical features seen in PBC, female ARE-Del mice have moderate immune cell infiltration and bile duct destruction near hepatic portal tracts with dramatically upregulated bile acids and spontaneous production of anti-mitochondria antibodies in serum. In contrast, male ARE-Del have relatively mild histological and serological evidences of PBC compared to female ARE-Del. By focusing on genes whose expression is highly specific to female ARE-Del, type I interferon receptor and dendritic maturation are top upstream pathways for this female specific disease progression. Remarkably, deletion of the interferon a/b receptor in ARE-Del mice significantly suppressed the female-specific pathological phenotypes, specifically eliminating the sex-different phenotypes in PBC. Furthermore, female ARE-Del have notably increased plasmacytoid dendritic cells (pDC), specialized in massive secretion of type I interferon (IFN alpha and beta), suggesting that increased type I interferon via pDC is critical for the sex-difference in this disease progression. Taken together, the ARE-Del is the first mice model to present the sex differences seen in PBC and startlingly demonstrates how type II interferon coordinates with type I interferon in this disease progression.